2015
DOI: 10.1002/2014jc010385
|View full text |Cite
|
Sign up to set email alerts
|

Hydro‐acoustic and tsunami waves generated by the 2012 Haida Gwaii earthquake: Modeling and in situ measurements

Abstract: Detection of low-frequency hydro-acoustic waves as precursor components of destructive tsunamis can enhance the promptness and the accuracy of Tsunami Early Warning Systems (TEWS). We reconstruct the hydro-acoustic wave field generated by the 2012 Haida Gwaii tsunamigenic earthquake using a 2-D horizontal numerical model based on the integration over the depth of the compressible fluid wave equation and considering a mild sloped rigid seabed. Spectral analysis of the wave field obtained at different water dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…In the last decade, studies have shown the advantages to be gained by taking the compressibility of water into account in describing the behavior of the water column in a tsunami source region (Levin & Nosov, ). Also, hydroacoustic waves generated by tsunamigenic sources due to the compressibility of water column gain attentions by many researchers as tsunami precursor as a component of Tsunami Early Warning Systems (Abdolali et al, ; Cecioni et al, ; Stiassnie, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, studies have shown the advantages to be gained by taking the compressibility of water into account in describing the behavior of the water column in a tsunami source region (Levin & Nosov, ). Also, hydroacoustic waves generated by tsunamigenic sources due to the compressibility of water column gain attentions by many researchers as tsunami precursor as a component of Tsunami Early Warning Systems (Abdolali et al, ; Cecioni et al, ; Stiassnie, ).…”
Section: Introductionmentioning
confidence: 99%
“…The earthquake hypocenter was localized at 14 km depth, 52.788 N, 132.101 W on the boundary between the Pacific and North America plates [ Cassidy et al ., ]. The ODP889BPR is located about 590 km south of the Haida‐Gwaii epicenter and was reached less than 2 min after the event by the seismic signal, after less than 7 min by the hydro‐acoustic signal generated by the earthquake [ Chierici et al ., ; Abdolali et al ., , Oliveira and Kadri , ; Bagheri et al ., ] and after 55 min by the tsunami wave (Figure , top plot original data). Black line in the middle panel of Figure shows the output of the TDA process performed by the algorithm resulting from the real‐time band‐pass filtering applied to the detided data.…”
Section: Resultsmentioning
confidence: 99%
“…Current AGW models consider simple geometries and displacements of bottom motions. Example of these motions include rectangular disturbances with constant [Nosov, 1999;Chierici et al, 2010;Stiassnie, 2010;Hendin and Stiassnie, 2013] or variable velocities [Yamamoto, 1982;Nosov and Kolesov, 2007;Abdolali et al, 2015a] in the two-dimensional problem, or circular disturbances with constant velocities in the three-dimensional case [Hendin and Stiassnie, 2013].…”
Section: Key Pointsmentioning
confidence: 99%
“…If the compressibility of the ocean is considered, a disturbance at the ocean floor may generate Acoustic-Gravity Waves (AGWs), progressive compression-type waves that travel at near the speed of sound in water. Recent studies indicate that as AGWs travel they leave measurable bottom pressure signatures that can act as tsunami precursors [Stiassnie, 2010;Chierici et al, 2010;Kadri and Stiassnie, 2012;Hendin and Stiassnie, 2013;Cecioni et al, 2014;Abdolali et al, 2015a]. In this regard, it is anticipated that such utilization of AGWs would enhance current early tsunami detection systems.…”
Section: Introductionmentioning
confidence: 99%